Starbucks : a story of growth - Garthwaite, Craig L., (SAGE knowledge. Cases., 2016)
Founded in 1971 and acquired by CEO Howard Schultz in 1987, Starbucks was an American success story. In forty years it grew from a single-location coffee roaster in Seattle, Washington to a multibillion-dollar global enterprise that operated more than 17,000 retail coffee shops in fifty countries and sold coffee beans, instant coffee, tea, and ready-to-drink beverages in tens of thousands of grocery and mass merchandise stores. However, as Starbucks moved into new market contexts as part of its aggressive growth strategy, the assets and activities central to its competitive advantage in its retail coffee shops were altered or weakened, which made it more vulnerable to competitive threats from both higher and lower quality entrants. The company also had to make decisions on vertical integration. This case study discusses these issues.